Devaluation with exchange rate floor in a small open economy - David Svacina (Charles University in Prague, Institute of Economic Studies (IES), 2018)
In recent years, central banks in the Czech Republic and Switzerland used exchange rate floor commitment to use unlimited FX interventions to keep the exchange rate above the declared floor rate to persistently devalue their currency and stimulate inflation. Central banks in other small open economies, such as Sweden and Israel, faced similar challenges and could have chosen this instrument as well. In this paper, I develop an extension to dynamic stochastic general equilibrium (DSGE) models that could be used to esimate impact of such devaluations with exchange rate floor. As an illustration, I apply the extension to models estimated for Sweden and the Czech Republic. In particular, I simulate impact of a 5 percent devaluation with the exchange rate floor used as an unconventional monetary policy instrument with interest rates at the zero lower bound. In the first year after the devaluation, the annual consumer price in inflation increases by 0.8 percent in Sweden and 1.8 percent in the Czech Republic. The long-term exchange rate pass-through to consumer prices is 40 percent and 65 percent, respectively. The increase in inflation is highly dependent on the persistent nature of the devaluation.
Keywords: E31; E37; E58; F41; 330; Exchange Rate Floor; Devaluation of Currency; Unconventional Monetary Policy Instrument; Dynamic Stochastic General Equilibrium Models; Exchange Rate Pass-Through